Prevalência de leveduras da espécie Saccharomyces cerevisiae na produção de etanol: seleção de linhagens promissoras para o melhoramento da eficiência produtiva - Silva, Dario Sampaio da (Universidade Federal de São Carlos, 2026)
Fuel ethanol production in Brazil relies on the performance of industrial Saccharomyces cerevisiae yeasts, which are subjected to successive stresses during the fermentative process. In this study, twenty industrial strains were evaluated through the integration of molecular and physiological analyses, using strain CAT-1 as a control, with the aim of selecting promising strains for industrial application. Molecular analyses confirmed the identity of the strains as S. cerevisiae and revealed high genetic diversity, with the formation of four main genotypic groups, in addition to strains displaying unique genotypic profiles. Physiological performance, assessed based on growth profiles in different media, enabled the calculation of the Total Performance Index (TPI), highlighting strains 2018-12, 2018-08, 2023-02, and 2022-13 as exhibiting superior growth compared to the control. Acid stress tolerance, evaluated through viability and cell concentration after acid treatment, was integrated into the Acid Treatment Tolerance Index (ATI), identifying strains 2022-15 and 2023-06 as among the most resistant. The combined analysis of TPI and ATI allowed the classification of the strains into three distinct physiological profiles: high growth performance with low acid tolerance; high acid tolerance with moderate performance; and a balanced profile between growth and stress tolerance. In this context, strains 2022-13 and 2022-04 stood out for their balanced performance, emerging as the most promising candidates for application in industrial ethanol production processes. These results demonstrate that the integration of molecular and physiological approaches is an efficient strategy for selecting yeasts adapted to the industrial fermentative environment.
Prevalence of Saccharomyces cerevisiae yeasts in ethanol production: selection of promising strains for improving production efficiency
Keywords: Saccharomyces cerevisiae; Etanol combustível; ITS; Genotipagem; Perfil de crescimento; Tratamento ácido; Linhagens promissoras; CIENCIAS BIOLOGICAS::MICROBIOLOGIA::MICROBIOLOGIA APLICADA::MICROBIOLOGIA INDUSTRIAL E DE FERMENTACAO; 7. Energia limpa e acessível